2015
DOI: 10.5380/avs.v20i3.39679
|View full text |Cite
|
Sign up to set email alerts
|

Programas De Luz Para Suínos Em Crescimento

Abstract: Foi realizado um experimento com o objetivo de avaliar o uso de programas de luz sobre o desempenho e comportamento de suínos em fase de crescimento. O experimento foi conduzido no setor de suinocultura da UFLA, em Lavras, MG, utilizando-se 48 suínos machos castrados com peso médio inicial de 29,99±0,05kg e final de 76,66±0,84kg, alojados em grupos de dois em cada baia, compondo a unidade experimental. Os animais foram distribuídos em delineamento de blocos casualizados, de acordo com o peso inicial em quatro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
1
2
0
1
Order By: Relevance
“…These authors also mention that when confined, pigs are more likely than other farmed animals to spend time resting and sleeping. Ferreira et al (2015) studied the behavior of growing pigs in relation to lighting conditions their results corroborate those of the present study, since they found that idling was more frequent in comparison with other behaviors, with an average of 87.64% of the time (corresponding to 21.03 hours per day) spent in this way. The present study found lower mean values (5.33 hours/day for WDP, and 6.16 hours/day for SLS).…”
Section: Wdp Slssupporting
confidence: 89%
See 1 more Smart Citation
“…These authors also mention that when confined, pigs are more likely than other farmed animals to spend time resting and sleeping. Ferreira et al (2015) studied the behavior of growing pigs in relation to lighting conditions their results corroborate those of the present study, since they found that idling was more frequent in comparison with other behaviors, with an average of 87.64% of the time (corresponding to 21.03 hours per day) spent in this way. The present study found lower mean values (5.33 hours/day for WDP, and 6.16 hours/day for SLS).…”
Section: Wdp Slssupporting
confidence: 89%
“…Animal welfare, environmental issues and food safety are currently considered to be the three biggest challenges in the pig sector. In view of this, there is significant concern regarding the influence of the environment on the comfort, welfare and performance of the animals (Ferreira et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the frequency of the animals at the drinker showed that it was higher for those housed in pens with forced ventilation, both during the day and during the night, and the treatment with 12 hours of light was the one that most stood out (Figure 4E), which does not agree with the results reported by Amaral et al (2014), who observed longer time in the "drinking" activity in animals under periods of prolonged lighting. However, Ferreira et al (2015) reported that growing pigs spent more time on visits to the drinker when exposed to the longest lighting period, but without differing statistically. Animals housed in pens with no climate control and with evaporative cooling spent more time on visits to the drinker at night (Figure 4D and 4F).…”
Section: Resultsmentioning
confidence: 94%
“…Recentemente, ambiência, segurança alimentar e bem-estar animal são uns dos maiores desafios relacionados à atividade. Todavia, segundo Ferreira et al (2015), há maior preocupação com a implicação que o ambiente pode exercer sobre o desempenho e comportamento dos animais.…”
Section: Introductionunclassified